2017
DOI: 10.20892/j.issn.2095-3941.2017.0052
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on nanoparticle-based drug delivery systems for cancer therapy

Abstract: The development of cancer nanotherapeutics has attracted great interest in the recent decade. Cancer nanotherapeutics have overcome several limitations of conventional therapies, such as nonspecific biodistribution, poor water solubility, and limited bioavailability. Nanoparticles with tuned size and surface characteristics are the key components of nanotherapeutics, and are designed to passively or actively deliver anti-cancer drugs to tumor cells. We provide an overview of nanoparticle-based drug delivery me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(112 citation statements)
references
References 80 publications
0
112
0
Order By: Relevance
“…Nanodrug delivery systems have always been a research hotspot for targeted therapy. All kinds of nanoparticles made by proteins, macromolecules or other materials have been shown to have positive therapeutic value (Xin et al, 2017;Zhang et al, 2019a,b). However, the possible biological toxicity and sensitization of medical macromolecule polymers used in drug delivery systems need to be solved before they can be clinically applied (Nouman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nanodrug delivery systems have always been a research hotspot for targeted therapy. All kinds of nanoparticles made by proteins, macromolecules or other materials have been shown to have positive therapeutic value (Xin et al, 2017;Zhang et al, 2019a,b). However, the possible biological toxicity and sensitization of medical macromolecule polymers used in drug delivery systems need to be solved before they can be clinically applied (Nouman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A small phase I pilot showed that NC-6004 was acknowledged by carcinoma patients that were affected by colorectal carcinoma, upper oesophageal carcinoma, and lung carcinoma [69]. The Genexol-PM formulation was a micellar PTX nanoformulation formulated from PEG with polylactic acid [68,134,135]. Preclinical in vivo trials with Genexol-PM formulation exhibited a threefold increase in average dissolution time and a significantly improved antineoplastic efficacy as compared with clinical paclitaxel [69].…”
Section: Nanomicelles In Clinical Evaluationsmentioning
confidence: 99%
“…Chemical neuromodulation techniques use either implantable devices, focused ultrasound, lipophilic vesicles, or nanoparticle formulations to overcome the blood-brain barrier and ensure delivery of adequate chemical concentrations to targeted neural compartments (see [76] and references therein). The state-of-the-art solutions for brain pathologies involve the application of nanoparticles synthesized from various materials (e.g., polymers, lipids, and viruses) [77]- [79]. By using either passive or active targeting strategies, nanoparticles can increase the intracellular concentration of drugs in neurons via receptor-mediated endocytosis while preventing toxicity to other cells.…”
Section: A State-of-the-artmentioning
confidence: 99%